2020
DOI: 10.3390/en13133379
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical and Economic Evaluation of Low-Cost Deep Eutectic Solvents for Effective Biogas Upgrading to Bio-Methane

Abstract: This paper presents the theoretical screening of 23 low-cost deep eutectic solvents (DESs) as absorbents for effective removal of the main impurities from biogas streams using a conductor-like screening model for real solvents (COSMO-RS). Based on thermodynamic parameters, i.e., the activity coefficient, excess enthalpy, and Henry’s constant, two DESs composed of choline chloride: urea in a 1:2 molar ratio (ChCl:U 1:2), and choline chloride: oxalic acid in a 1:2 molar ratio (ChCl:OA 1:2) were selected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 62 publications
2
22
0
Order By: Relevance
“…The conductor-like screening model for real solvents (COSMO-RS) was used to calculate the solubility of siloxanes in pure glycols and water and in DESs composed with TPABr and glycols. Based on the previous studies, it can be deduced that COSMO-RS is a useful tool for solvent screening and predicting the impurities’ solubility in conventional as well as non-conventional solvents [ 35 , 41 , 42 ]. In most of the published works, the selection of solvents is made on certain parameters, i.e., Henry’s constant and activity coefficient.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The conductor-like screening model for real solvents (COSMO-RS) was used to calculate the solubility of siloxanes in pure glycols and water and in DESs composed with TPABr and glycols. Based on the previous studies, it can be deduced that COSMO-RS is a useful tool for solvent screening and predicting the impurities’ solubility in conventional as well as non-conventional solvents [ 35 , 41 , 42 ]. In most of the published works, the selection of solvents is made on certain parameters, i.e., Henry’s constant and activity coefficient.…”
Section: Resultsmentioning
confidence: 99%
“…The results are often inconsistent. However, the most important parameter from the industrial point of view, solubility, is rarely reported [ 35 , 43 ]. Therefore, in this study, we calculated the solubility of individual siloxanes (L2, L3, and D4) in various DESs composed of TPABr as HBA and glycols, i.e., ethylene glycol (EG), glycerol (Gly), triethylene glycol (TriEG), tetraethylene glycol (TEG), and diethylene glycol (DEG), as HBD at various molar ratios (1:3; 1:4; 1:5; 1:6, HBA:HBD).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, ILs are costly, and this is a significant hurdle for their large-scale commercial applications. Deep eutectic solvents (DES) have been introduced and considered as another class of ILs (Alkhatib et al, 2020;Słupek et al, 2020). Although DESs have the same characteristics as ILs, the price is significantly lower than ILs (Pena-Pereira and Namieśnik, 2014; Kamgar et al, 2017), making them more attractive for large-scale applications.…”
Section: Introductionmentioning
confidence: 99%